دور وأهمية هيئة الاستثمار السورية في إعادة البناء والإعمار - سلمان, حيان (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تعتبر الاستثمارات بشكل عام الحامل الحقيقي والفعلي لمقومات التنمية المجتمعية العامة الشاملة، هذه التنمية التي تولدّ عوامل قوتها من ذاتها وبذاتها ولذاتها، وتزداد أهمية التدفقات الاستثمارية في الظروف الصعبة القاسية التي تمر فيها أي دولة كما هو عليه الآن في سورية، وخاصة أنها تعرضت وتتعرض لخسائر كبيرة من جراء هذه الحرب الظالمة التي شنت عليها منذ 15/3/2011 ولذلك تتجسد الأولوية حاليا أمام السياسة الاقتصادية بشكل عام في تحسين المؤشرات الاقتصادية من معدل النمو الاقتصادي والناتج المحلي الإجمالي وتحسين الميزان التجاري وزيادة الاحتياطيات النقدية وغيرها، وسياسة هيئة الاستثمار السورية بشكل خاص في تحفيز الاستثمارات الداخلية والخارجية وجذبها الى سورية، هذا هو جوهر ومضمون بحثنا.Investments are generally real and actual swatch of overall community development، development that generate power from factors and of itself and of itself، the importance of investment flows in difficult circumstances with which that State as it is now in Syria، and especially that she was subjected to significant losses as a result of this unjust war waged since March 15، 2011، and therefore reflected the priority of economic policy generally improving economic indicators of economic growth rate and GDP and improving The balance of trade and increase cash reserves and others، Syrian investment body policy particularly stimulating domestic and foreign investment and attracted to Syria، and that is the essence and substance of our research.